The microeconomics of the AIDS epidemic in Africa - Philipson, T.; Posner, R. a.
tbls., gráfs.
pp. 835-848
Keywords: Africa al Sur del Sahara; Sida, Sindrome de Inmunodeficiencia Adquirida; Aspectos Economicos; Morbilidad; Mortalidad